2012
DOI: 10.1097/pdm.0b013e318241117b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Molecular Analysis and Histopathology for Axillary Lymph Node Staging in Primary Breast Cancer

Abstract: In breast cancer, the number of lymph node metastases is the strongest predictor of outcome. However, histopathology may underestimate the frequency of metastasis. Here we compare automated molecular detection of cytokeratin 19 mRNA by one-step nucleic acid amplification (OSNA) with histopathology of single tissue sections for the staging of axillary lymph nodes in patients with breast cancer. Axillary lymph nodes were collected from 55 patients with primary breast cancer and sentinel lymph node (SLN) metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The authors state that one-level histology was chosen to reflect the minimum standard used in many laboratories. 51 The study by Choi et al 53 reported a sensitivity of 77.8% (95% CI 60% to 90%) for OSNA, which is comparatively low. The authors indicate that this is likely to be the result of TAB; however, the dissection of the node was carried out using a similar method to that used in other studies.…”
Section: Single-gate Studiesmentioning
confidence: 97%
See 4 more Smart Citations
“…The authors state that one-level histology was chosen to reflect the minimum standard used in many laboratories. 51 The study by Choi et al 53 reported a sensitivity of 77.8% (95% CI 60% to 90%) for OSNA, which is comparatively low. The authors indicate that this is likely to be the result of TAB; however, the dissection of the node was carried out using a similar method to that used in other studies.…”
Section: Single-gate Studiesmentioning
confidence: 97%
“…Sixteen test accuracy papers were included for OSNA, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] with two papers reporting the same study. Two unpublished papers 40,66 for Metasin were identified and assessed using the Standards for the Reporting of Diagnostic Accuracy Studies (STARD) in Table 7.…”
Section: Number and Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations